PERAN ETIKA PROFESI GURU DALAM MEMBANGUN SUASANA PEMBELAJARAN YANG MENDUKUNG BAGI ANAK USIA DINI - Dea Ayu Febriana; Kayla Maylisa Yusman; Nur Khasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Professional ethics of teachers is a crucial component in the implementation of early childhood education (ECE). The role of teachers is not limited to merely delivering learning materials, but also as primary role models in shaping children’s character. This study aims to analyze the role of teachers’ professional ethics in creating a conducive learning environment for early childhood. The method applied is a literature review with a qualitative approach, drawing on scientific journals and relevant books published between 2017 and 2025. The results of the analysis indicate that the implementation of professional ethical values—such as responsibility, empathy, honesty, and professionalism—makes a significant contribution to the creation of a safe, comfortable, and enjoyable learning environment. Such a conducive learning environment is able to optimally support children’s cognitive, socio-emotional, and moral development. Therefore, strengthening teachers’ professional ethics becomes an essential element in efforts to improve the quality of early childhood education.